2016
DOI: 10.17796/1053-4628-40.6.472
|View full text |Cite
|
Sign up to set email alerts
|

Dentin Topographic Features following Chemomechanical Caries Removal in Primary Teeth

Abstract: Papacarie produced a rough and porous surface with partial or complete removal of the smear layer and opened dentinal tubules, while the drill produced a smooth surface with uniform smear layer occluding the dentinal tubules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…However, when Carisolv ® has been used over carious dentin, the surface generally appeared clean, with open tubules [22]. The same is likely to be true for Papacárie, since many studies have also reported similar residual carious dentin surface morphology after it use, with open tubules and reduced smear layer [23][24][25]. Nonetheless, one study showed presence of smear layer and debris partially occluding the dentin tubules in residual carious primary teeth dentin after caries removal with Papacárie Duo Gel ® [26].…”
Section: Discussionmentioning
confidence: 96%
“…However, when Carisolv ® has been used over carious dentin, the surface generally appeared clean, with open tubules [22]. The same is likely to be true for Papacárie, since many studies have also reported similar residual carious dentin surface morphology after it use, with open tubules and reduced smear layer [23][24][25]. Nonetheless, one study showed presence of smear layer and debris partially occluding the dentin tubules in residual carious primary teeth dentin after caries removal with Papacárie Duo Gel ® [26].…”
Section: Discussionmentioning
confidence: 96%
“…Structural changes associated with prepared dentin may influence the bonding of restorative materials and most of the studies have established that CMCR produces a roughened surface with altered hardness. 4,5 Glass ionomer cement is still the preferred restorative material for restoring primary teeth, but there are no studies evaluating the bond between the glass ionomer cement with the residual dentin following caries removal using Carie Care TM . The present study was thus planned to evaluate the bond between the resin-modified glass ionomer cement and residual dentin following excavation of carious dentin using Carie Care TM and conventional caries removal in primary teeth.…”
Section: Introductionmentioning
confidence: 99%
“…Structural changes associated with prepared dentin may influence the bonding of restorative materials and most of the studies have established that CMCR produces a roughened surface with altered hardness. 4 , 5 …”
Section: Introductionmentioning
confidence: 99%
“…When dental caries is removed using traditional rotary devices, the pulp is frequently subjected to pressure and heat effects that usually cause pain. In addition, drilling could sometimes involve the removal of sound tooth tissue close to the affected caries area [3,4]. Alternative minimally invasive techniques such as ART and chemomechanical caries removal (CMCR) were developed due to the shortcoming of the drill.…”
Section: Introductionmentioning
confidence: 99%